Memória e identidade na formação de professores leitores: relato de uma experiência com a escrita memoriográfica - Ferreira Cavalcante, Ilane (Confluenze. Rivista di Studi Iberoamericani, 2013)
This work focus on the experience of teaching Portuguese in the Spanish teaching degree at Instituto Federal de Educação, Ciências e Tecnologia do Rio Grande do Norte (IFRN). The main point of the experience was writing a memorial essays about the most important books they read during their lives, books that marked their formation as readers. Fragments of these essays are analyzed here using the theoretical construct of memory, developed by Bosi (1999), and the theoretical constructs of identity discussed by Pollack (1997) and Hall (2006).